Education, poverty and income transfer programs: The implementation of the Oportunidades Program in Mexico - Breynner Ricardo Oliveira; Maria do Carmo de Lacerda Peixoto (Arizona State University, 2019)
This article analyzes the implementation of the Oportunidades Program in Mexico based on the perspective of the local agents linked to the educational conditionality. By adopting the bottom up approach to analyzing implementation, Lipsky's (1980) formulation is the main reference for the study. Education professionals, community promoters and the representatives of the holders are those that correspond to the characterization of the author in this case. Forty-seven interviews were conducted: 9 with the strategic and managerial body at the national and state levels; 38 with local agents (2 with health professionals, 14 with school actors, 10 with agents linked to family support, and 12 with vocales.) The guidelines for the interviews were adapted according to their position in the hierarchy of the program and covered the following dimensions: institutional conditions and operation, perceptions about the program and its targets, impressions on the educational conditionality and the demands placed on local actors. Data show that budget constraints, oscillations in the hierarchy of social priorities and political control and dependence reveal aspects that are directly linked to the formation of the Mexican State and society.